Pagar Laut dan Eksklusi Masyarakat Pesisir: Kajian Literatur atas Ketimpangan Akses di PIK Tangerang - Rusdianto, Megawati; Watunnaba, Nuris (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
When a dumping policy is in place, it affects pulp exports to South Korea, but after the dumping policy is no longer in effect, it has no effect on Indonesian pulp exports to South Korea. The construction of a sea wall in the Pantai Indah Kapuk (PIK) area, Tangerang, has raised multidimensional issues involving the social exclusion of coastal communities, environmental degradation, and alleged legal irregularities in the permitting process. This study employs a literature review method to analyze the impacts of the project through Hilary Silver’s theory of social exclusion. Silver conceptualizes exclusion as a complex, multidimensional process involving the severance of access to resources, political participation, and social integration. The findings show that the sea wall, both physically and symbolically, separates coastal residents—particularly fishers—from their living space and means of livelihood. Disrupted fishing routes, increased operational costs, and damage to coastal ecosystems are among the direct consequences felt by the local community. Moreover, the lack of transparency and the potentially illegal nature of the development reinforce structural inequalities and disregard the rights of communities to space and participation. This study recommends the enforcement of spatial justice, reform of coastal development governance, and the active involvement of local communities in the planning and implementation of coastal policies.